Hospitalization and bed occupancy rate in a COVID-19 intensive care unit - da Silva Santos, Débora Aparecida; Galantini, Brenda Stephany; Pauletto Sales, Monara; Silveira Goulart, Letícia; de Mattos, Magda; Alves de Olinda, Ricardo (O Mundo da Saúde, 2022)
Most people develop mild or moderate symptoms of COVID-19, but some people develop severe symptoms, leading to hospitalizations. The objective of the research was to analyze the prevalence of confirmed cases of COVID-19, hospitalization for this disease in Intensive Care Units, and the occupancy rate of beds resulting from the same in these units in the municipality of Rondonopolis, Mato Grosso. This was a cross-sectional, descriptive study with a quantitative approach, with data from secondary sources of epidemiological bulletins in Rondonopolis, Mato Grosso, from June 2020 to May 2021. The average number of hospitalized cases per month and the occupancy rate of intensive care beds were calculated. All cases reported with COVID-19 and hospitalized in the Intensive Care Unit of public hospitals in the municipality were included. Analyses were performed with R Software and the chi-square goodness-of-fit test and Kendall's correlation were performed. A total of 28,443 new cases of COVID-19 were reported during the study period, with the highest average of hospitalizations in the intensive care unit in the public health network was in May 2021 (n=51.1) and the bed occupancy rate was in September 2020 (129.17%). In all regions analyzed in comparison with this study, the ICUs operated in a state of calamity with high occupancy rates. A relationship between the increase in the number of cases and hospitalizations and occupancy rates of Intensive Care Units was identified, which are findings that indicate the need to control COVID-19.